Hypernatraemic dehydration in children with acute gastroenteritis requiring intensive care in a tertiary hospital, Cape Town, South Africa. - Abu-Hajer, Hasan (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMed)--Stellenbosch University, 2023.